DEPROTEINATION OF CHITIN FRESH-WATER CLAM SHELLS (Pilsbryoconcha exilis) BY USING PAPAIN ENZYM - Muhammad Kamal Akbar; Edison Edison; Andarini Andarini (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACTFreshwater mussleclamsis one of the mollusks that is originated in freshwater. The meat of the Freshwater mussle clams was widely consumed but itsshells werestill unused and so becoming as the waste. However, clamshells have the potential to become a chitin product.The production of chitin and chitosan in the deproteination process using chemical method can damage the quality of the chitin and chitosan. This study aimed to determine the best concentration of papain enzymes fortheclamshells deproteination. The treatment conducted in this research was in the using of papain enzyme at different concentrations (15%, 20%, and 25%) for the deproteination process of clamshell. The amount of protein hydrolyzed was determined by using Kjeldahl method.The results obtained the best chitin characteristics in the K3 treatment, namely levels3.23% water, 7.45% ash content, and 4.60% protein contentKeywords:Chitin, Deacetylation, deproteination, Freshwater mussleclams, Papain enzym